Integration of IoT, Automation, and Real-Time Analytics for Intelligent Pressure Control in Industry 5.0 Smart Manufacturing - Mohanty, Anita; Mohapatra, Ambarish G.; Kumar Mohanty, Subrat; Alhayan, Fatimah; Alanazi, Rakan; Mujib Alshahrani, Mohammed; Burhanur Rehman, Mohammed; Gupta, Deepak (IEEE transactions on consumer electronics, 2025)
The modern industrial revolution started when Industry 4.0 shifted to Industry 5.0 through the adoption of intelligent control strategies designed to promote sustainable operations with human-machine partnership. The research presents a noise-driven pressure control architecture based on fuzzy-PID controllers that combines IoT devices alongside real-time processing and an adjustable control mechanism for advanced manufacturing environments. The conventional use of PID controllers presents issues, as they encounter problems related to nonlinearities and slow dynamics, as well as manually set parameters, which lead to performance problems. Adaptive control actions resulting from fuzzy logic implementation enable the proposed system to respond better to process variations, thereby improving both efficiency and accuracy, together with response speed. The system structure includes predictive maintenance features alongside uninterrupted monitoring capabilities and cloud-based analytics that gain favourable results for reliability and scalability. Through its implementation, the system supports Industry 5.0 standards by offering holographic 3D visual interfaces and pressure system management through intuitive human control. The experimental setup containing dual pneumatic vessels proved that the proposed system outperforms typical PID controllers because it reaches higher accuracy at faster settling times with lower overshoot. The analysis addresses important problems, including data protection and system connection capabilities, as well as real-time response during industrial system changes in dynamic conditions. The combination of Industry 5.0 technologies with fuzzy control intelligence enables the proposed approach to optimize sustainability levels and reduce operational expenses, as well as increase process adaptability. The research delivers an advanced pressure control system based on human element integration, which meets the changing requirements of future industrial automation.